HADRONIC ENERGY-DISTRIBUTIONS IN DEEP-INELASTIC ELECTRON-PROTON SCATTERING - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Repond, S; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayad, R; Bari, G; et al. (1993)
This paper presents energy distributions of the hadronic system produced in neutral-current electron-proton deep-inelastic scattering at a centre of mass energy of 296 GeV. Comparison of the results with QCD Monte Carlo models shows that QCD radiation has a strong influence on the characteristics of the final state. The data are reasonably reproduced by the Lund model based on a matrix element calculation in first order of αs, followed by appropriate parton showers, as well as by the colour dipole model. The HERWIG parton shower model also gives a reasonable representation of the data. Neither the first order matrix elements alone nor the Lund parton shower model, without the matrix element calculation, reproduce the data. © 1993 Springer-Verlag.